(3eG CTcd aj GdcJH GdKdGKI (B( (3GdehWC hGdHNGQi heSde (B)s - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s ((3GdeOQSI GdcGedjI HGdbGgQI s)
(3ChdgG (B:s
(3gPG GdcJGH jTJed Ydi KdGKI CHhGH GdHGH GdChd ai PcQ Led hbY ajgG JUMja Ch WeS eYfGgG s
(3BNQgG (B:s
(3hai HGH hChdGJ GdCMeGd MOjK aCfJ Cf JfcMg abGd hGddg eG jUdM Cf JfcMjg gPG gh UMjMg cedJ GdRjGOI Ydi GdCHhGH GdKdGKI hHceGdgG ced LejY cJGH eTGQb GdCfhGQ hGdMeO ddg JYGdi Mb MeOg s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1687s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs